Redesigning organic catalysts and polymers for recycling towards sustainable catalysis and materials - Cywar, Robin Marcelle, author; Chen, Eugene Y.-X., advisor; Beckham, Gregg T., advisor; Reynolds, Melissa M., committee member; Borch, Thomas, committee member; Peebles, Christie A. M., committee member (Colorado State University. Libraries, 2021)
This dissertation describes the development of catalysts and polymers designed for a sustainable, circular materials economy in which end-of-life is considered during the design stage through properties of inherent recyclability. Products that are recyclable-by-design contrast with those of the current, linear economy, which has led to global environmental crises: greenhouse gas emissions due to finite fossil fuel consumption, contributing to climate change, and tremendous accumulations of plastic waste in landfills and the environment. A major challenge associated with the development of circular lifecycle products, including both catalysts and polymers (plastics, in particular), is achieving performance properties competitive with those of their incumbents, which this work aimed to address. A critical literature review provides an overview of materials derived from renewable, biomass feedstocks (referred to as bio-based polymers) which exhibit performance-advantaged properties relative to petroleum-based polymers. Bio-based chemicals and materials are considered to have a circular carbon lifecycle (carbon-neutral), but those with a circular lifecycle (i.e., recyclable or biodegradable) are given special emphasis. To increase the circularity of all aspects of production of bio-based chemicals and polymers, a polymer-supported organocatalyst has been explored for the coupling of biomass-based furaldehyde platform chemicals; these products can be used for bio-fuels or polymers after further transformations. The developed thermally activated N-heterocyclic carbene (NHC) organocatalyst can be recycled for furfural coupling in excellent yield simply by controlling the temperature, demonstrating promising features for improved circularity in catalyzed chemical processes and ultimately, waste reduction. The discovery of acid-base interactions between the catalyst and hydroxylated substrates has enhanced the understanding of NHC catalysis and contributed to improved design principles for these catalysts. To address plastic waste accumulation by designing for recyclability, polyester and polyamide materials with full chemical recyclability to monomers have been demonstrated from lactone and lactam monomers, respectively. In each case, study of polymerization activity through chemical catalysis revealed fundamental information about the thermodynamic (de)polymerizability of the novel systems, including selectivity considerations, and enabled synthesis of robust structural models for thermomechanical characterization. Overall, understanding the resultant structure-property relationships informs further development of materials with full chemical recyclability and attractive materials properties, including copolymer formulations and design of new monomers to explore for addressing tradeoffs between (de)polymerization activity and material properties.
Keywords: chemical recyclability; design for recyclability; bio-based polymers; supported organocatalyst; circular polymers